Some Difficulties in the Epistemology of Understanding: McDowell vs Dummett - Japertas, Mindaugas (Problemos, 2012)
The article discusses the justification of John McDowell’s “anti-anti-realist” view towards Michael Dummett’s philosophy of anti-realism. In spite of Dummett’s intention to base his anti-realism (and philosophy at large) on considerations belonging to the theory of meaning, philosophy of language, and metaphysics, McDowell discloses in his forerunner’s arguments a more fundamental and independent “epistemological framework” – a quite traditional, inappropriate and even illusory “epistemology of understanding”. It should be noted that both philosophers share the view as to the understanding of mathematical sentences: both of them support anti-platonism and believe that the notion of responsiveness to decidable circumstances must be central in the epistemology of mathematics. However, McDowell dissents from Dummett’s attempt to generalize this proper model of the epistemology of mathematics, that is, to apply it in an account of understanding the language outside mathematics. Generalized anti-realism (anti-realism about the natural world) can arise only due to a certain epistemological idea, namely, the hankering for “solid”, independently ascertainable, presupposition-free foundations that would serve as a guarantee for the understanding of our utterances.McDowell dismisses this epistemological idea as the “epistemological prejudice” and he opts for a “less ambitious” epistemology according to which the understanding of the linguistic practice presupposes the prior involvement in the very practice – equipment with command of a language. The perspective of a comprehending participant is the only suitable for theorizing about the relation of our language to the world.
Keywords: Dummett; McDowell; anti-realism; language; understanding; epistemology